PILAR PENDIDIKAN DASAR: ANALISIS PENGEMBANGAN FISIK HINGGA KREATIFITAS DI SEKOLAH DASAR - Alfi Fauziyatus Tsani; Moh Hafilul Akbar; Ammar Rijal (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research focuses on developing the basics taught in elementary schools using a qualitative approach method, with observational data collection techniques and data collection processes through analysis and content. The results of this research succeeded in revealing several types of basic development taught in elementary schools, including physical development, cognitive development, social development, emotional development, language and communication development, creativity and imagination development. The conclusion from the results of this research is that several types of development taught in elementary schools are important developments to be mastered and understood by students who are of productive age.